PANTUN MELAYU BANGKA: KAJIAN BENTUK, FUNGSI, DAN MAKNA - Sarman Sarman Sarman (Kantor Bahasa Lampung, 2020)
Abstract People of Bangka, one of Indonesia’s region, keeps using pantun in their various traditional and national activities. However, it is a deep concern that such oral traditions is about to extinct. Therefore, a study on pantun is important. This study aimed to examine the form, function, and meaning of the Malayan-Bangka pantun. This research used descriptive qualitative method and documentation techniques. Primary data source were speech and printed information. Secondary data sources were theory of stucture and meaning of poetry by I.A. Richard, theory of function by William R. Bascom, and theory of meaning (semantics) by Pateda. The research resulted that Malayan-Bangka pantun had a distinctive structure and inner structure of meaning. Besides, Malayan-Bangka pantun functioned as means of communication, identity, decorating oral traditions, education and sermon speech, embodiment of customs, entertainment, cultural symbols, cultivating heroism, as well as a means of connecting Malayan-Bangka community. Key words: Malayan-Bangka pantun, structure, function, and meaning